2003
DOI: 10.1034/j.1600-0722.2003.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of proliferation, apoptosis and keratin expression in cultured normal and immortalized human buccal keratinocytes

Abstract: The current study was undertaken to analyse growth and differentiation-related functions of normal keratinocytes (NOK) and an SV40T-immortalized keratinocyte line (SVpgC2a) from buccal mucosa, viewing the latter cell line as a model of a dysplastic epithelium. Morphological and immunohistochemical assessments of organotypic epithelia generated from 10 or 17 d of culture showed three- to five-fold higher apoptotic and proliferative activity in SVpgC2a relative to NOK. Conditions with or without serum (up to 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…This was in line with previous experiments in melanoma cells (21). A spontaneous induction of Ck's 8 and 18 expression could be shown in SV40T-immortalized buccal mucosa cells, in tobacco induced leukoplakia and after introduction of v-H-Ras in epidermal mouse keratinocytes (22). The involvement of Ck 8/18 in SCC progression could further be demonstrated in chemically induced SCCs in the mouse skin.…”
Section: Discussionmentioning
confidence: 68%
“…This was in line with previous experiments in melanoma cells (21). A spontaneous induction of Ck's 8 and 18 expression could be shown in SV40T-immortalized buccal mucosa cells, in tobacco induced leukoplakia and after introduction of v-H-Ras in epidermal mouse keratinocytes (22). The involvement of Ck 8/18 in SCC progression could further be demonstrated in chemically induced SCCs in the mouse skin.…”
Section: Discussionmentioning
confidence: 68%
“…In oral carcinomas, the proportion of active caspase‐3‐positive cells with apoptotic morphology was markedly higher than in normal oral epithelium, confirming the findings of Macluskey et al 26 that the apoptotic index is increased during oral carcinogenesis. Hansson et al 27 showed that in organotypic culture, the immortalized buccal epithelial cell line, SVpgC2a, consistently exhibited a greater apoptotic index than normal oral keratinocytes. We found that active caspase‐3 staining facilitated the scoring of apoptotic index in oral tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes were cultured on dermal equivalents composed of type I collagen and fibroblasts and raised to the air-medium interface to promote differentiation. This model has also been applied to keratinocytes derived from the oral cavity, including buccal (16,17,33,34,73), lingual (38), and peritonsillar (62) surfaces. Several of these studies underscored the importance of fibroblasts located in adjacent connective tissue, which provide permissive and instructive signals to differentiating keratinocytes (64,77).…”
Section: Discussionmentioning
confidence: 99%